Find the value of 1 ⋅ 3 1 + 2 ⋅ 4 1 + 3 ⋅ 5 1 + 4 ⋅ 6 1 + …
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
GREAT SOLUTION!! same way
I did the same way. Nice solution
We have a general pattern: n ( n + 2 ) 1 = 2 1 ( n 1 − n + 2 1 ) Our expression becomes: 2 1 ( 1 1 − 3 1 ) + 2 1 ( 2 1 − 4 1 ) + 2 1 ( 3 1 − 5 1 ) … = 2 1 ( 1 − 3 1 + 2 1 − 4 1 + 3 1 − 5 1 … ) = 2 1 ( 1 + 2 1 ) = 4 3
The following sum can be expressed as r = 1 ∑ ∞ r ( r + 2 ) 1 . We will try to split this into two separate fractions:
Suppose r ( r + 2 ) 1 = r A + r + 2 B ⇒ 1 = A ( r + 2 ) + B r .
Let r = − 2 . Then 1 = − 2 B ⇒ B = − 2 1 .
Let r = 0 . Then 1 = 2 A ⇒ A = 2 1 .
∴ r = 1 ∑ ∞ r ( r + 2 ) 1 = r = 1 ∑ ∞ 2 r 1 − 2 ( r + 2 ) 1 = ( 2 1 − 6 1 ) + ( 4 1 − 8 1 ) + ( 6 1 − 1 0 1 ) + ( 8 1 − 1 2 1 ) + … = 2 1 + 4 1 = 4 3
Problem Loading...
Note Loading...
Set Loading...
The n th term of the series is a n = n ( n + 2 ) 1 = 2 1 ( n 1 − n + 2 1 ) .
Thus n = 1 ∑ ∞ n ( n + 2 ) 1 = 2 1 n = 1 ∑ ∞ ( n 1 − n + 2 1 ) = 2 1 ( 1 + 2 1 + n = 3 ∑ ∞ ( n 1 − n 1 ) ) = 2 1 ∗ 2 3 = 0 . 7 5 .